(untitled) (Journal of Gender and Social Issues, 2023)
The twenty-first century is considered the age of digital revolution. Digital literature is considered the product of the postmodern era. Exposure to digital technologies and access to various cultures has changed the way themes and stories are presented in digital or electronic literature for children. These changes are not only the result of development in technology but also the influence of postmodernism. This paper studies digital literature created for children to explore the influence of postmodernism. The digital text chosen for analysis is Red Riding Hood (2001) by Dona Leishman. The study aims to determine how digital literature appropriates a classical text and offers perspectives on gender and social roles through various elements that it employs. Postmodernism comprises a large number of issues. In this study postmodernism is taken to mean challenging of metanarratives, existence of chaos in the world and blurring of boundaries.